Clinical comparison of brachytherapy versus hypofractionated external beam radiation versus standard fractionation external beam radiation for non-melanomatous skin cancers - Haseltine, Justin M; Parker, Matthew; Wernicke, A. Gabriella; Nori, Dattatreyudu; Wu, Xian; Parashar, Bhupesh (Journal of Contemporary Brachytherapy, 2016)
Purpose : Non-melanomatous skin cancer (NMSC) is the single most common cancer in the US. Radiation therapy is an excellent treatment alternative to surgery. High-dose-rate (HDR) brachytherapy and external beam radiotherapy (EBRT) are commonly used radiation treatment modalities but little data is published comparing these modalities. We present our institution’s experience and outcomes with these therapeutic options. Material and methods : From June 2005 to March 2013, 61 patients were treated with HDR brachytherapy (n = 9), hypofractionated EBRT (n = 30), or standard fractionation EBRT (n = 22) for NMSC. The primary outcome measure was local control at most remote follow-up and secondary outcome measures were overall survival, cosmetic outcome, and toxicity. Univariate analysis was performed to compare outcomes between treatment modalities. Kaplan-Meier analysis and log-rank test were used to compare overall survival. Results : Median follow-up was 30 months. The most common histologies were BCC (47%) and SCC (44%); mean patient age was 83.3 years. Local control was 81% and 2-year actuarial overall survival was 89%. There was no statistical difference in local control or overall survival between treatment modalities. There was no statistical difference in cosmetic outcome or toxicity between treatment modalities, although five of six “poor” cosmetic outcomes and the only grade 3 toxic events were found in the standard fractionation EBRT group. Conclusions : All modalities investigated represent effective treatments for NMSC and have good cosmetic outcomes and acceptable toxicity profiles. The finding of higher grade toxicity and a greater portion of patients experiencing toxicity among standard fractionation therapy is counter to expectations. There was no statistical significance to the finding and it is not likely to be meaningful.